On-orbit real-time magnetometer bias determination for micro-satellites without attitude information - Zhang, Zhen; Xiong, Jianping; Jin, Jin (Chinese journal of aeronautics, 2015)
Due to the disadvantages such as complex calculation, low accuracy of estimation, and being non real time in present methods, a new real-time algorithm is developed for on-orbit mag- netometer bias determination of micro-satellites without attitude knowledge in this paper. This method uses the differential value approach. It avoids the impact of quartic nature and uses the iterative method to satisfy real-time applications. Simulation results indicate that the new real-time algorithm is more accurate compared with other methods, which are also tested by an experiment system using real noise data. With the new real-time algorithm, a magnetometer calibration can be taken on-orbit and will reduce the demand for computing power effectively.